Evolution of the life cycle primary PM2.5 emissions in globalized production systems. (October 2019) - Zhang, Haoran; Li, Ruixiong; Chen, Bin; Lin, Huiming; Zhang, Qianru; Liu, Maodian; Chen, Long; Wang, Xuejun
Abstract: Production system-related air pollution emissions are dominant components in global emission reduction targets and in realizing relevant sustainable development goals (SDGs). To better understand the air pollution emissions induced by globalized production systems through a life cycle perspective, environmental extended multiregional input-output (EE-MRIO) analysis was applied to calculate the primary product-based emissions and the final product-based emissions embodied in the global production systems. Combined with two types of linkage analysis, named the hypothetical extraction method (HEM) and the emissions pure backward linkage (EPBL), emissions were analysed at three scopes at the sector level from macro sector linkage perspectives. An illustrative analysis was presented based on the global EXIOBASE MRIO database and primary PM2.5 emissions from 1995 to 2011. The results show that from 1995 to 2011, the primary PM2.5 emissions in the global production systems increased by 35%. In 2011, China's production system generated the highest primary product-based and final product-based primary PM2.5 emissions, which accounted for 30.7% and 29.6% of the global total, respectively. The emission flows balance between primary product-based emissions and final product-based emissions revealed that most developing countries are sources of emissions and that developed countries are sinks of emissions in production systems. An approximately U-shaped relationship was found in the primary PM2.5 emissions embodied in final products, while the opposite relationship was found embodied in primary products. Meanwhile, sector-specific protocols for controlling the high indirect emissions sectors can make the supply chain cleaner. Our findings further indicated that focusing more on industries can help relevant emissions control policymaking processes. Highlights: Life cycle production system-related air pollution was calculated. Final product-based emissions were identified. Relationships between the embodied emissions with economic growth were revealed. Linkage analysis was applied to calculate the scope emissions.